1993
DOI: 10.1152/jn.1993.70.4.1401
|View full text |Cite
|
Sign up to set email alerts
|

In vitro electrophysiology of developing genioglossal motoneurons in the rat

Abstract: 1. Experiments were performed to determine the change in membrane properties of genioglossal (GG) motoneurons during development. Intracellular recordings were made in 127 GG motoneurons from rats postnatal ages 1-30 days. 2. The input resistance (R(in)) and the membrane time constant (t(aum)) decreased between 5-6 and 13-15 days from 84.8 +/- 25.4 (SD) to 47.0 +/- 18.9 M omega (P < 0.01) and from 10.0 +/- 4.2 to 7.3 +/- 3.3 ms (P < 0.05), respectively. During this period, the rheobase (Irh) increased (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
38
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 0 publications
11
38
2
Order By: Relevance
“…5B and 7C), similar to what has been described in HMs in the rodent brain stem in previous studies (Nunez-Abades et al 1993;van Brederode and Berger 2008;Viana et al 1995). HMs in this study showed either little or no frequency adaptation or frequency acceleration due to a long first ISI.…”
Section: Firing Patterns In Response To Depolarizing Current Stepssupporting
confidence: 90%
“…5B and 7C), similar to what has been described in HMs in the rodent brain stem in previous studies (Nunez-Abades et al 1993;van Brederode and Berger 2008;Viana et al 1995). HMs in this study showed either little or no frequency adaptation or frequency acceleration due to a long first ISI.…”
Section: Firing Patterns In Response To Depolarizing Current Stepssupporting
confidence: 90%
“…Throughout this report we refer to animals ՅP8 as neonates and animals ՆP20 as juveniles. Previous reports have indicated that many of the electrophysiological properties of HMs are adult-like by this stage (Núñez-Abades et al, 1993;Bayliss et al, 1994a,c;Viana et al, 1994;Berger et al, 1996), and we consider it likely that data from these juvenile animals are representative of adults.…”
Section: Methodsmentioning
confidence: 79%
“…It is becoming increasingly apparent that integrative properties of motoneurons, as well as the neurotransmitter mechanisms by which those properties are modulated, also undergo significant changes during the early postnatal period (for review, see Berger et al, 1996). This plasticity reflects differential expression of ion channels during development (Núñez-Abades et al, 1993;Bayliss et al, 1994a;Viana et al, 1994) as well as the modulation of those ion channels by neurotransmitters at any given developmental stage (ZiskindConhaim et al, 1993;Bayliss et al, 1994c;Funk et al, 1995). Moreover, the modulatory neurochemical systems that impinge on motoneurons are not static; their chemical phenotype and projection patterns also can change throughout development (Ziskind-Conhaim et al, 1993;Bayliss et al, 1994c).…”
mentioning
confidence: 99%
“…The aim of this study was to directly compare effects of riluzole at a maximal clinically relevant dose on the range of factors controlling motor neuron excitability by electrophysiological recording from HMs. Electrophysiological recordings of membrane potential, resistance, holding current, repetitive firing and single action potential properties, voltage-sensitive persistent Na ϩ and Ca 2ϩ currents, evoked, spontaneous, and miniature excitatory synaptic potentials, and postsynaptic responses to glutamate were made with whole cell patch-clamp techniques in rat HMs in in vitro brain stem slices from rats aged 10 -23 days, a period when HM morphology (Núñez-Abades et al 1994) and electrical excitability (Berger et al 1995;Núñez-Abades et al 1993) have matured sufficiently to assume or be close to their adult properties.…”
mentioning
confidence: 99%